Transcriptome Analysis of Pineal Glands in the Mouse Model of Alzheimer’s Disease - Nam, Kwang Il; Yoon, Gwangho; Kim, Young-Kook; Song, Juhyun (Frontiers in Molecular Neuroscience, 2020)
The pineal gland maintains the circadian rhythm in the body by secreting the hormone melatonin. Alzheimer’s disease (AD) is the most common neurodegenerative disease. Pineal gland impairment in AD is widely observed, but no study to date has analyzed the transcriptome in the pineal glands of AD. To establish resources for the study on pineal gland dysfunction in AD, we performed a transcriptome analysis of the pineal glands of AD model mice and compared them to those of wild type mice. We identified the global change of diverse protein-coding RNAs, which are implicated in the alteration in cellular transport, protein transport, protein folding, collagen expression, histone dosage, and the electron transfer system. We also discovered various dysregulated long noncoding RNAs and circular RNAs in the pineal glands of mice with AD. This study showed that the expression of diverse RNAs with important functional implications in AD was changed in the pineal gland of the AD mouse model. The analyzed data reported in this study will be an important resource for future studies to elucidate the altered physiology of the pineal gland in AD.